Hijab butch blues ebook A memoir. - H, Lamya (2023)
A queer hijabi Muslim immigrant survives her coming-of-age by drawing strength and hope from stories in the Quran in this “raw and relatable memoir that challenges societal norms and expectations” (Linah Mohammad, NPR). “A masterful, must-read contribution to conversations on power, justice, healing, and devotion from a singular voice I now trust with my whole heart.”—Glennon Doyle, #1 New York Times bestselling author of Untamed THEM ’S HONOREE IN LITERATURE • AN AUDACIOUS BOOK CLUB PICK • WINNER: The Brooklyn Public Library Book Prize, the Stonewall Book Award, the Israel Fishman Nonfiction Award • Lambda Literary Award Finalist A BEST BOOK OF THE YEAR: NPR, Autostraddle, Book Riot, BookPage, Harper’s Bazaar, Electric Lit, She Reads When fourteen-year-old Lamya H realizes she has a crush on her teacher—her female teacher—she covers up her attraction, an attraction she can’t yet name, by playing up her roles as overachiever and class clown. Born in South Asia, she moved to the Middle East at a young age and has spent years feeling out of place, like her own desires and dreams don’t matter, and it’s easier to hide in plain sight. To disappear. But one day in Quran class, she reads a passage about Maryam that changes everything: When Maryam learned that she was pregnant, she insisted no man had touched her. Could Maryam, uninterested in men, be . . . like Lamya?   From that moment on, Lamya makes sense of her struggles and triumphs by comparing her experiences with some of the most famous stories in the Quran. She juxtaposes her coming out with Musa liberating his people from the pharoah; asks if Allah, who is neither male nor female, might instead be nonbinary; and, drawing on the faith and hope Nuh needed to construct his ark, begins to build a life of her own—ultimately finding that the answer to her lifelong quest for community and belonging lies in owning her identity as a queer, devout Muslim immigrant.   This searingly intimate memoir in essays, spanning Lamya’s childhood to her arrival in the United States for college through early-adult life in New York City, tells a universal story of courage, trust, and love, celebrating what it means to be a seeker and an architect of one’s own life.